Colonialism and Hybrid Political System: A Case of Pakistan - Younis, Muhammad (Pakistan Languages and Humanities Review, 2024)
The purpose of this study is to investigate the impact of military and bureaucracy on Pakistan's politics by using politics of memory and colonialism as theoretical frameworks to interpret both historical as well as contemporary trajectories. This research seeks to discover how colonial legacies continue to influence contemporary practices of democracy by examining the effects of electoral rigging and military interventions on political stability. Pakistan, despite having some features of democracy, can best be declared a hybrid state where the core institutions like armed forces and bureaucracy predominantly shape and reshape the political and democratic discourse of both the state and the society. On the problems and challenges of hybrid democracy in Pakistan, this research is of the view that the Pakistani political system and democracy have not been decolonized since its inception in 1947. It is therefore strongly recommended that Pakistan should decolonize its political system to establish effective democratic infrastructure.